Temporal and Spatial Change of Juvenile Crimes in Taif Governorate during the Period 2015-2020 - Al-Zahrani, Mohammed Rajab (Journal of Humanities & Social Sciences, 2021)
The study aimed to highlight the temporal and spatial change of juvenile crimes in the Taif Governorate during the period from 2015-2020. To achieve its objectives, the study relied on the data of the Ministry of Human Resources and Social Development– Juvenile Welfare Department 2020. The study adopted the inductive-inferential approach as a methodological framework, using statistical methods and modern techniques in graphs and cartography. The study found that the crimes decreased very sharply from 33.3% to 2.8%, and the results showed that the two crimes of self and money were at the top of the list of juvenile crimes. As for the nationalities of the perpetrators of these crimes, except for Saudis, 17 nationalities participated in them, as the Yemeni community formed the highest percentage (22%), followed by Burmese nationality (16%) of the total nationalities. In terms of the spatial distribution of the crime, Al- Hawiyah and Al- Faisaliyah police stations occupied the largest percentage among the police departments by about (43%) for both of them. Based on the results, the study recommends conducting more juvenile crime studies, focusing on self and money crimes.